Construct and Predictive Validity of Social Acceptability: Scores From High School Teacher Ratings on the School Intervention Rating Form. (April 2016) - Harrison, Judith R.; State, Talida M.; Evans, Steven W.; Schamberg, Terah
The purpose of this study was to evaluate the construct and predictive validity of scores on a measure of social acceptability of class-wide and individual student intervention, the School Intervention Rating Form (SIRF), with high school teachers. Utilizing scores from 158 teachers, exploratory factor analysis revealed a three-factor (i.e., Suitability, Perceived Benefit, Convenience) structure. Findings revealed that teachers who implemented class-wide and individual student interventions with perfect integrity or less than acceptable integrity rated the interventions as less suitable than those who implemented with acceptable integrity. Similarly, the same groups rated the interventions as less convenient than those who implemented with acceptable integrity. Implications for practice and future research are discussed.